2012
DOI: 10.1016/j.chemosphere.2012.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological effects on earthworms of fresh and aged nano-sized zero-valent iron (nZVI) in soil

Abstract: Although nano-sized zero-valent iron (nZVI) has been used for several years for remediation of contaminated soils and aquifers, only a limited number of studies have investigated secondary environmental effects and ecotoxicity of nZVI to soil organisms. In this study we therefore measured the ecotoxicological effects of nZVI coated with carboxymethyl cellulose on two species of earthworms, Eisenia fetida and Lumbricus rubellus, using standard OECD methods with sandy loam and artificial OECD soil. Earthworms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(40 citation statements)
references
References 49 publications
0
35
0
2
Order By: Relevance
“…However, despite the low cost and high efficiency of Fe 0 NPs in removing contaminants, [1][2][3][4][5][6] there are concerns that Fe 0 NP application contributes to long-term impacts on environmental and human health risks. [7][8][9][10][11][12][13][14][15][16][17] Moreover, the increasing use of Fe 0 NPs in in situ groundwater remediation could lead to large numbers of NPs released into the environment and is highly likely to pose potential exposure risks. 8 Several studies have indicated that Fe 0 NPs could cause cytotoxicity in human bronchial epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the low cost and high efficiency of Fe 0 NPs in removing contaminants, [1][2][3][4][5][6] there are concerns that Fe 0 NP application contributes to long-term impacts on environmental and human health risks. [7][8][9][10][11][12][13][14][15][16][17] Moreover, the increasing use of Fe 0 NPs in in situ groundwater remediation could lead to large numbers of NPs released into the environment and is highly likely to pose potential exposure risks. 8 Several studies have indicated that Fe 0 NPs could cause cytotoxicity in human bronchial epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the usage of omics methods (e.g. Jones et al 2008) for the toxicity assessment and measuring the effects of emerging pollutants in earthworms, especially nanoparticles and nanomaterials (Hu et al 2010(Hu et al , 2014Heckmann et al 2011;Hooper et al 2011;Shoults-Wilson et al 2011a, b;El-Temsah and Joner 2012;Tsyusko et al 2012;Hayashi et al 2013), provided new aspects of toxicant effects on earthworms. The assessment of the effects of these pollutants on soil ecosystems is mainly in the initial stage.…”
Section: Advances In Earthworm Ecotoxicologymentioning
confidence: 99%
“…Moreover, the fertility of the soil will be influenced because Fe 2+ will substitute for heavy metal cations in the process of remediation, which will lead to a high Fe content in the soil. Some published papers have shown that too much Fe in soil was detrimental to plants and was disadvantageous for replanting (Mengel 1994;Chen et al 2012;El-Temsah and Joner 2012;Ma et al 2013). In order to overcome these problems in iron phosphate nanoparticle soil remediation, the use of biochar was proposed in this study.…”
Section: Introductionmentioning
confidence: 95%